(509) ميزانية النقد الأجنبي (مادة تحليلية)Foreign Exchange Budget (Analytical Material) - ألفونس عزيز (معهد التخطيط القومي, 2026)
تتناول هذه المذكرة التعليمية تطور وأهمية "ميزانية النقد الأجنبي" في مصر كأداة استراتيجية لمواجهة ندرة الموارد المالية الخارجية وتنظيم استخدامها بما يخدم خطط التنمية الاقتصادية. يستعرض البحث المراحل التاريخية لسياسات النقد، بدءاً من فرض الرقابة على الصرف عام 1939 والخروج من منطقة الاسترليني، مروراً بتبني نظام الميزانية النقدية رسمياً عام 1957 لمواجهة الحصار الاقتصادي عقب العدوان الثلاثي، وصولاً إلى تطوير أدوات مثل "حسابات حق الاستيراد" و"السوق الموازية للنقد الأجنبي" لجذب المدخرات ودعم الصادرات.، كما يفصل الملف الجوانب المنهجية لإعداد الميزانية النقدية، مبيناً الفوارق بينها وبين ميزان المدفوعات، حيث تعتبر الميزانية خطة تقديرية مستقبلية للموارد (كالصادرات المنظورة وغير المنظورة) والاستخدامات (كالاستيراد السلعي والوفاء بالالتزامات الدولية). ويشرح البحث بالنماذج والجداول الإحصائية دور الوزارات المختلفة (المالية، التجارة، والزراعة) في تقدير حصيلة الصادرات وتوزيع الاعتمادات المالية على القطاعات، مع التأكيد على ضرورة التنسيق الربع سنوي لمتابعة تنفيذ الميزانية وضمان التوازن بين الموارد المتاحة والاحتياجات القومية لتجنب أي اختناقات اقتصادية تعوق مسيرة التنمية. This educational memorandum examines the evolution and importance of the "foreign exchange budget" in Egypt as a strategic tool for addressing the scarcity of external financial resources and regulating their use to serve economic development plans. The research reviews the historical stages of monetary policies, beginning with the imposition of exchange controls in 1939 and the exit from the Sterling Area, through the official adoption of the monetary budget system in 1957 to counter the economic blockade following the Tripartite Aggression, and culminating in the development of tools such as "import rights accounts" and the "parallel foreign exchange market" to attract savings and support exports. The memorandum also details the methodological aspects of preparing the monetary budget, highlighting the differences between it and the balance of payments. The budget is considered a future projection plan for resources (such as visible and invisible exports) and expenditures (such as commodity imports and fulfilling international obligations). Using models and statistical tables, the research explains the role of various ministries (Finance, Trade, and Agriculture) in estimating export revenues and allocating financial appropriations to sectors. It emphasizes the necessity of quarterly coordination to monitor budget implementation and ensure a balance between available resources and national needs to avoid any economic bottlenecks that could hinder development.